2016
DOI: 10.1007/s00038-016-0796-x
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe smoking among secondary school students in Hong Kong

Abstract: Waterpipe smoking was the most popular alternative tobacco product among Hong Kong adolescents. Despite the low prevalence, it should be routinely monitored. Education programs and cessation interventions need to address waterpipe smoking in addition to cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Consistent with existing studies [39][40][41], our result found actively smoking cigarettes was associated with past 30 days waterpipe use. Poly tobacco/nicotine product use is common among current cigarettes smokers [42].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with existing studies [39][40][41], our result found actively smoking cigarettes was associated with past 30 days waterpipe use. Poly tobacco/nicotine product use is common among current cigarettes smokers [42].…”
Section: Discussionsupporting
confidence: 93%
“…Waterpipe (1.2%, 95% CI: 1.1-1.4%) and e-cigarettes (1.1%, 95% CI: 1.0-1.3%) were the most popular ATPs used by students, followed by cigars (1.1%, 95% CI: 0.9-1.2%), chewing tobacco (0.8%, 95% CI: 0.7-1.0%), snus (0.6%, 95% CI: 0.5-0.7%), and nasal snuff (0.5%, 95% CI: 0.4-0.6%) and other noncigarette tobacco products (0.4%, 95% CI: 0. 4 27 . This finding is alarming.…”
Section: Discussionmentioning
confidence: 99%
“…The Survey was approved by the Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster. Details regarding the Survey have been described elsewhere 27,28 . The 2012/13 Survey was conducted from October 2012 to April 2013.…”
Section: Data Sourcementioning
confidence: 99%
“…The smoke then bubbles through a jar filled with water and is ultimately inhaled. Although waterpipe smoking is a cultural custom in many Middle‐Eastern countries such as Bahrain, Lebanon, Qatar, Saudi Arabia, and United Arab Emirates; this form of smoking has gained popularity, particularly among the youth, in many Western countries including Hong Kong, Sweden, United Kingdom, and the United States . Results from a recent study showed that waterpipe smoking is not less harmful than cigarette smoking, and waterpipe smokers (WS) are as susceptible to periodontal destruction as conventional cigarette smokers (CS).…”
Section: Introductionmentioning
confidence: 99%
“…Although waterpipe smoking is a cultural custom in many Middle-Eastern countries such as Bahrain, Lebanon, Qatar, Saudi Arabia, and United Arab Emirates; [13][14][15][16] this form of smoking has gained popularity, particularly among the youth, in many Western countries including Hong Kong, Sweden, United Kingdom, and the United States. [17][18][19][20] Results from a recent study 14 showed that waterpipe smoking is not less harmful than cigarette smoking, and waterpipe smokers (WS) are as susceptible to periodontal destruction as conventional cigarette smokers (CS). Similarly, in a clinical study on dental implants, Al-Harthi et al 13 compared the peri-implant soft tissue inflammatory parameters (plaque index [PI], bleeding on probing [BOP], probing depth [PD], and CBL) among WS, CS, and never-smokers (NS).…”
Section: Introductionmentioning
confidence: 99%